A Framework for Predictable Hardware/Software Component Reconfiguration - Reis, João Gabriel; Bezerra, Eduardo Augusto; Fröhlich, Antônio Augusto (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2017: Anais do XXX Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2017.3460, 2017)
The current pace of innovation in computing makes it difficult to assume a fixed set of requirements for the whole life span of a system. Aggressive technology scaling also imposes additional constraints to modern hardware platforms. Field-Programmable Gate Array (FPGA) reconfiguration can help systems cope with dynamic requirements such as performance and power, hardware defects due to Negative-Bias Temperature Instability (NBTI) and Process, Voltage and Temperature (PVT) variations, or application requirements unforeseen at design time. This work proposes a framework for reconfigurable components whereby the reconfiguration of a component implementation is performed transparently without user intervention. The reconfiguration process is confined in system's idle time without interfering with or being interfered by other activities occurring in the system or even peripherals performing I/O. A telecommunications switch was used as a case study for the deployment of reconfigurable components as well as the impact I/O interference has in the process and to explore non-functional trade-offs between implementations.